An assessment of task-technology fit, subjective norm and internet experience of Learning Management System in views of Malaysian higher education Students - Baleghi-Zadeh, Sousan; Mohd Ayub, Ahmad Fauzi; Mahmud, Rosnaini; Mohd Daud, Shaffe (IRPN Press, 2014)
In recent years, the use of Learning Management System (LMS) in higher education has dramatically increased. However, many students use LMS for limited purposes such as downloading course materials. There are many factors that may affect LMS utilization by students. In the present study three factors, namely Internet experience, subjective norm, and task-technology fit were examined. The participants of the study were 216 undergraduate students of faculty of education in one of the local universities in Malaysia. The results revealed that the constructs of Internet experience and subjective norm obtained a high mean value. This result suggests students who used LMS have a sufficient internet experience which could easily help them in using it. University and lecturer support seems to be the most important sources that encourage them to use LMS. Students also responded their satisfaction with the functionality of LMS to assists them in the process of learning.